5a³ - 4ab + 2a³ = (5+2)a³ - 4ab = 7a³ - 4ab.
(4ab^2 + 3cd)(4ab^2 - 3cd)
4a2 + 4ab - y2 + b2 You cannot simplify this expression because it does not contain like terms, but you can factor it such as: 4a2 + 4ab - y2 + b2 = (4a2 + 4ab + b2) - y2 = (2a + b)2 - y2 = [(2a + b) - y][(2a + b) + y]
It is: 2a(2b+c)
The greatest common factor of 4ab and 6ab is 2ab. You simply take the greatest common factor from both factors. The greatest common factor of 4 and 6 is 2. The letters can be factored out because they appear in both factors
2a*2b = 4ab
6a2 + 5ab - 6b2 = 6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)*(3a - 2b)